2014
DOI: 10.1186/1475-2875-13-170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing reveals substantial Plasmodium vivax infection in asymptomatic adults in a rural area of Cameroon

Abstract: BackgroundMalaria in Cameroon is due to infections by Plasmodium falciparum and, to a lesser extent, Plasmodium malariae and Plasmodium ovale, but rarely Plasmodium vivax. A recent report suggested “Plasmodium vivax–like” infections around the study area that remained unconfirmed. Therefore, molecular and antigenic typing was used to investigate the prevalence of P. vivax and Duffy in asymptomatic adults resident in Bolifamba.MethodsA cross-sectional study was conducted from July 2008 to October 2009. The stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
90
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 33 publications
9
90
4
1
Order By: Relevance
“…Till 2013, incidences of P. vivax infection reported in Cameroon were restricted to non-native Cameroonians [22]. Very recently, it has been found that native Cameroonians ( Duffy positive as well as Duffy negative individuals) were also able to be infected by the malaria parasite P. vivax [23]. Considering Cameroon as “Africa in miniature” with respect to malaria epidemiology [21], the recent report on native Cameroonians being infected with P. vivax [23] and the fact that Cameroon borders with malaria endemic countries (such as Equatorial Guinea) reporting P. vivax infection in Duffy -negative individuals, it is therefore important not only to survey the extent of malaria due to infection of different species of malaria parasites in native Cameroonians, but also to explore other regions of the country for the possible detection of P. vivax malaria infection.…”
Section: Introductionmentioning
confidence: 99%
“…Till 2013, incidences of P. vivax infection reported in Cameroon were restricted to non-native Cameroonians [22]. Very recently, it has been found that native Cameroonians ( Duffy positive as well as Duffy negative individuals) were also able to be infected by the malaria parasite P. vivax [23]. Considering Cameroon as “Africa in miniature” with respect to malaria epidemiology [21], the recent report on native Cameroonians being infected with P. vivax [23] and the fact that Cameroon borders with malaria endemic countries (such as Equatorial Guinea) reporting P. vivax infection in Duffy -negative individuals, it is therefore important not only to survey the extent of malaria due to infection of different species of malaria parasites in native Cameroonians, but also to explore other regions of the country for the possible detection of P. vivax malaria infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Duffy-null individuals were found to be infected with P. vivax, both throughout Africa (Kenya, Madagascar, Mauritania, Cameroon, Angola, Equatorial Guinea, Ethiopia, and Sudan) and in South America (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), raising the question: How can P. vivax invade in the absence of Duffy blood group expression? Is it possible that mutations in the cysteine-rich region 2 of the P. vivax DBP1 allows binding to another protein on the surface of Duffy-null erythrocytes, unrelated to the Duffy?…”
Section: Dna Expansionmentioning
confidence: 99%
“…Misdiagnosis, mixed-parasitic infection, and successful establishment and continuous spread of resistant parasite strains pose a great challenge for global malaria control programs. Hence, accurate diagnosis appears to be crucial for the successful treatment of malaria, and molecular approaches by polymerase chain reaction (PCR) diagnostic assays have lately evolved, across the world, as the most sensitive method for this purpose in comparison to the traditional microscopy method [2][3][4][5][6]. In addition, Plasmodium vivax is now capable of not only infecting Africans, who are ordinarily recognized as resistant to malaria infection due to this parasite, but also of causing severe malaria [7].…”
mentioning
confidence: 99%
“…In addition, Plasmodium vivax is now capable of not only infecting Africans, who are ordinarily recognized as resistant to malaria infection due to this parasite, but also of causing severe malaria [7]. In this respect, newer studies have reported that Duffy-negative native Cameroonians can also be infected by P. vivax [5,6]. These P. vivax-infected patients were found in five different cities of the southern part of the country [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation